PRODUÇÃO E COMPOSIÇÃO DO LEITE DE VACAS GIR E GUZERÁ NAS DIFERENTES ORDENS DE PARTO - Adelílian Baracho Ribeiro; André Fernandes da Fonseca Tinoco; Guilherme Ferreira; Magda Maria Guilhermino; Adriano Henrique do Nascimento Rangel (Revista Caatinga, 2009)
The present study aimed to evaluate the interference of cows genotype and calving order on the milk production and composition during lactation period. Thirty six cow (19 Gir and 17 Guzera) were the studied population, analyzed from October 2005 to February 2008. Gir and Guzera cows showed no significant differences between daily milk production amount of milk produced in 305 days and of lactation duration. There were significant differences in milk fat for Gir and Guzer multiparous, and milk protein for Gir and Guzer primiparous and multiparous. Multiparous Gir cow showed higher lactose rate than Guzera cow. Calving order among cows that multiparous produced milk containing higher fat levels than cow at first giving birth. Total solid (TS) end nonfat dry extract (NDE) was significantly different of both primiparous and multiparous animals between genotypes, except for TS primiparous cows. It was used Student-T test to compare different milk characteristics between genotypes and calving order, setting at 5%. In conclusion, the calving order and genotype do not affect Gir and Guzera milk production, but however, milk composition was interference.